2018
DOI: 10.15760/comminfolit.2018.12.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Everything Online is a Website: Information Format Confusion in Student Citation Behaviors

Abstract: The ability to effectively cite information sources is key to both student avoidance of plagiarism and the ongoing scholarly conversation. Previous research and experience indicated that students had significant trouble distinguishing and citing various information formats when viewed online; items are often cited as websites, and citations are incomplete or contain erroneous and extraneous information. The authors investigated the prevalence of these problems at their university, seeking out common patterns i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Our results indicate that many of our students perceived any materials assigned together in their LMS as a single unit of "course materials" -almost as though their LMS has become both course and textbook in their eyes. This kind of container collapse is discussed in librarianship already in how we teach patrons to identify, evaluate, and use distinct kinds of information sources (Cyr et al, 2021;Greer & McCann, 2018;Brannon et al, 2021). Because the markers that differentiate sources of various publishing formats are not always as clear in digital spaces as they would be in print, we often need to help students discern between sources like magazine articles, newspaper articles, blogs, eBooks, and scholarly research articles.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that many of our students perceived any materials assigned together in their LMS as a single unit of "course materials" -almost as though their LMS has become both course and textbook in their eyes. This kind of container collapse is discussed in librarianship already in how we teach patrons to identify, evaluate, and use distinct kinds of information sources (Cyr et al, 2021;Greer & McCann, 2018;Brannon et al, 2021). Because the markers that differentiate sources of various publishing formats are not always as clear in digital spaces as they would be in print, we often need to help students discern between sources like magazine articles, newspaper articles, blogs, eBooks, and scholarly research articles.…”
Section: Discussionmentioning
confidence: 99%
“…Holmes et al (2008) found that school-age children struggled to differentiate among the formats returned by their search. Greer and McCann (2018) found that undergraduate students do not recognize the differences between online formats and struggle to cite sources for their papers. There is also evidence to suggest that students are not using the format filters within the discovery system to navigate these complexities (Resau, 2019).…”
Section: Format In Information Seekingmentioning
confidence: 99%
“…Most commonly, however, format is used as a catch-all term to denote any formal element of an information resource that varies according to recognizable types (e.g., Association of College & Research Libraries [ACRL], 2016; Clark et al, 2018;Francke & Sundin, 2009;Greer & McCann, 2018;Quint, 1985). In this paper, we will use format in the more common general sense, with the understanding that in doing so, it is necessary to articulate the more specific elements of format that might fall under that umbrella.…”
Section: Limitations Of Previous Studiesmentioning
confidence: 99%
“…This did not provide readers with the perception of a published journal With so much exposure to the internet, students are beginning to experience what Greer and McCann call "format confusion" meaning that students now see everything as a website. 16 By having the journal in the repository with the individual articles, users did not recognize that the article was part of the bigger journal. One way to combat this was by adding a full issue in addition to the individual articles, so that users could see how the journal was actually put together.…”
Section: Identifying Challengesmentioning
confidence: 99%